Timing chromosomal amplification events using patterns of somatic mutations in high hyperdiploid acute lymphoblastic leukemia - Woodward, Eleanor; Yang, Minjun; Moura-Castro, Larissa Helena; van den Bos, Hilda; Gunnarsson, Rebeqa; Arvidsson, Linda Olsson; Spierings, Diana C. J.; Castor, Anders; Duployez, Nicolas; Zaliova, Marketa; Zuna, Jan; Johansson, Bertil; et al. (Lund University, 2023)
This dataset included 22 patients with high hyperdiploid acute lymphoblastic leukemia (ALL) collected from the Division of Clinical Genetics, Lund University, Sweden. All samples were subjected to whole genome sequencing by the Illumina HiSeqX platform. Paired-end sequencing (2x150bp) was done to ~60x coverage for diagnostic samples and ~30x coverage for remission. The paired-end reads were aligned to the human reference genome GRCh37 (https://www.ncbi.nlm.nih.gov/assembly/GCF_000001405.25/) by the Burrows-Wheeler Aligner tool (version 0.7.17). Duplicate reads marking and local realignment were performed by GATK (version 4.0.11.0). Somatic variants were identified by the GDC DNA-Seq analysis pipeline (Zhang et al.,2021). The data was stored in vcf format and the interpretation of the file is available at: https://docs.gdc.cancer.gov/Data/File_Formats/VCF_Format/.
Keywords: Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik